Die Verbindlichkeit der Freiheit: über das Verhältnis von Verbindlichkeit und Freiheit in der evangelischen Ethik - Huber, Wolfgang (Zeitschrift für evangelische Ethik, 1993)
Freedom ist a basic theme oftheological ethics. In protestant theology it is treated in different forms. They can be clarified by the different ways in which freedom is related to the obligatory force (Verbindlichkeit) of ethical decisions. Freedom as obligation, freedom as the only reason for obligation, and historization of all obligations in the name of freedom are the three typical concepts. The discussion on obligation itself entails also three main answers: The obligatory force ofthe given reality, the universal communicability of ethical norms and the sola scriptura are here the three typical concepts. The article pleads for a processual understanding of obligation in Christian ethics and uses as model the ecumenical concept of conciliarity. This concept shows a specific correspondence to the Christian understanding of freedom as communicative freedom.